2022
DOI: 10.1108/jpbm-07-2021-3560
|View full text |Cite
|
Sign up to set email alerts
|

Are product design researchers and practitioners on the same page? The way professional product designers view creative design

Abstract: Purpose This paper aims to explore professional product designers’ views on creative design and to compare their viewpoints with the related academic literature on product marketing. Design/methodology/approach To find the designers’ views on creative design, face-to-face in-depth interviews based on repertory grid analysis and semi-structured questions were conducted with 32 professional and award-wining product designers who mostly design for international producers. Findings Although marketing scholars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…The outcome was judged by the third author and then the differences were discussed until an agreement was reached. The interviews with the employees and managers lasted between 15 and 25 min (see Sameti et al. , 2022; Kim et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome was judged by the third author and then the differences were discussed until an agreement was reached. The interviews with the employees and managers lasted between 15 and 25 min (see Sameti et al. , 2022; Kim et al.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome was judged by the third author and then the differences were discussed until an agreement was reached. The interviews with the employees and managers lasted between 15 and 25 min (see Sameti et al, 2022;Kim et al, 2016). The inquiry was conducted in the Persian language for maximum understanding of the participants and the statements quoted below have been translated with great care through the cooperation of all the authors.…”
Section: The Initial Interviewmentioning
confidence: 99%
“…Human-Centric is an approach adopted for characteristics that describe the capability of design thinking (Mikalef et al, 2021) with the ability to work in cross-disciplinary teams (F. Zhang et al, 2020), even both of which are considered suitable for carrying out innovation. Due to the desired uniqueness related to design thinking skills, several researchers are currently planning to increase research to understand how design thinking actually can be developed (Auernhammer & Roth, 2021;Kamal et al, 2020;Meinel et al, 2020;Ravanello et al, 2017;Sameti et al, 2022). A model was developed by Acklin regarding the design management absorption model which aims to provide support to SMEs with or without previous design experience to develop a mindset regarding design thinking as well as an indicator to measure the progress of absorption (Ravanello et al, 2017).…”
Section: Business Organization : the Role Of Design Thinking In Produ...mentioning
confidence: 99%
“…Researchers Sameti, Koslow and Mashhady [11] compared 32 professional artists' opinions on design creativity with related academic literature and found that the artists view design as a problem-solving process to address customers' issues while academics approach to design as a collection of attributes, dimensions or characteristics that can be viewed and analysed. Similarly, Gera [16] stated that an academician is likely to frame problems and solutions in a theoretical and abstract context that appears unimportant and nonsensical to artists.…”
Section: Boundaries Of Artist and Academicmentioning
confidence: 99%